Pengaruh Pengetahuan, Tingkat Kepercayaan, dan Risiko Terhadap Minat Penggunaan Fintech Lending (Studi pada Pengguna Fintech Lending di Kecamatan Koto Tangah Kota Padang) - Vina Febyola; Dita Maretha Rissi; Vira Maulina (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2025)
The rapid growth of digital financial technology has encouraged the emergence of financial technology (Fintech) services, including Peer-to-Peer (P2P) Lending or Fintech Lending, which provides easier access to funding. However, the adoption of Fintech Lending in Indonesia, particularly in Koto Tangah District, Padang City, still faces challenges related to knowledge, trust, and risk. This study aims to analyze the influence of knowledge, level of trust, and risk on the intention to use Fintech Lending. Using a quantitative approach and survey method, data were collected from 105 MSME actors who actively use Fintech Lending services, specifically PNM Mekaar and Amartha in Koto Tangah District, Padang City, and analyzed using multiple linear regression with the assistance of SPSS. The results show that knowledge and trust have a positive and significant effect on the intention to use Fintech Lending, while risk has no significant effect. These findings indicate that better understanding and stronger trust in system security and service reputation increase users’ willingness to adopt Fintech Lending, while risk becomes less influential among users with adequate literacy. This study highlights the importance of digital education and system transparency to strengthen public trust in technology-based financial services.